ISSUES AND CHALLENGES IN THE ASSESSMENT OF CHILDREN IN NURSERY - Norazly Nordin; Muhammad Safar Abdurahman; Afina Nazira Afnizul (UPI Kampus Cibiru, 2021)
Assessment is a systematic and on-going process of attaining information about a child’s development and learning progress. Assessment is often conducted by professional educators in collaboration with parents through regular observation and several standardized tests. Assessment is very significant to identify the strengths and weaknesses to support and provided interventions needed by the child to elevate their development. Every nursery institution must implement the assessment process to ensure a well-balanced development of the children. Accordingly, a qualitative study using the interview method was conducted in a private nursery in the state of Selangor involving a nursery owner, a supervisor, and four educators to identify issues and challenges faced in implementing the assessment. The results found that many aspects including the educator’s competence, cooperation from parents, time constraint and record management are the main issues and challenges encountered in executing the assessment. The informants also suggested that continuous training and effort for educators and advocacy should be intesified to educate the community. It is also underlined that there is a need for the integration of Information and Communication Technology (ICT) to ensure the efficiency of the assessment process.